Climate Politics and the Impact of Think Tanks Scientific Expertise in Germany and the US - Ruser, Alexander (Springer International Publishing, 2018)
This book provides an innovative theoretical and analytical framework for studying the role and impact of specialized research organizations and consultancies on decision making in climate politics. It includes advanced empirical analysis of the case of Germany, compared with the situation in the USA. The book improves the understanding of the role and impact of 'scientific' advice in coping with the challenge of anthropogenic climate change. Alexander Ruser is currently a temporary Professor of Sociology and Head of the Center for Political Communication at Zeppelin University, Germany. He was a Dahrendorf fellow at the Hertie School of Governance in Berlin and Visiting Fellow at the London School of Economic and Political Science and the Punjab University, Chandigarh, India.